Experimental investigation on reverse cycle defrosting performance improvement for an ASHP unit by evenly adjusting the refrigerant distribution in its outdoor coil. (5th March 2017) - Song, Mengjie; Liu, Shengchun; Deng, Shiming; Sun, Zhili; Yan, Huaxia
Abstract: For an air source heat pump (ASHP) unit, reverse cycle defrosting operations are always conducted to solve the undesired frosting problem. Previous studies verified that, uneven refrigerant distribution (URD) and melted frost downwards flowing (MFDF) along the vertically installed multi-circuit outdoor coil would degrade system defrosting performance. However, it is hardly possible to separate the URD and MFDF effects in a practical multi-circuit outdoor coil. In addition, it is a fundamental coupled problem of uneven heat and mass transfer. Consequently, to investigate the coupled effects of MFDF and URD on system defrosting performance, a sequential experimental study is carried out and reported in this paper. Firstly, a special testing facility and tailor-made three-circuit outdoor coil were introduced. This is followed by two experimental cases designed, with frost evenly accumulated on the surface of each circuit by adjusting the stop valves' opening degrees. After the experimental results compared, basing on refrigerant evenly and unevenly distributed into each circuit, energy analysis was also given. Finally, as concluded, the coupled effects were negative on system energy performance, and defrosting efficiency increased by 7.4%, from 40.5% to 47.9%, when the refrigerant's distribution changed from uneven to even. This study makes contributions on the optimization of system control strategies.